Community perceptions of pre-eclampsia in rural Karnataka State, India: a qualitative study. Issue 1 (June 2016) - Vidler, Marianne; Charantimath, Umesh; Katageri, Geetanjali; Ramadurg, Umesh; Karadiguddi, Chandrashekhar; Sawchuck, Diane; Qureshi, Rahat; Dharamsi, Shafik; Dadelszen, Peter; Derman, Richard; Goudar, Shivaprasad; Mallapur, Ashalata; et al.
Abstract Background Maternal deaths have been attributed in large part to delays in recognition of illness, timely transport to facility, and timely treatment once there. As community perceptions of pregnancy and their complications are critical to averting maternal morbidity and mortality, this study sought to contribute to the literature and explore community-based understandings of pre-eclampsia and eclampsia. Methods The study was conducted in rural Karnataka State, India, in 2012–2013. Fourteen focus groups were held with the following community stakeholders: three with community leaders (n = 27), two with male decision-makers (n = 19), three with female decision-makers (n = 41), and six with reproductive age women (n = 132). Focus groups were facilitated by local researchers with clinical and research expertise. Discussions were audio-recorded, transcribed verbatim and translated to English for thematic analysis using NVivo 10. Results Terminology exists in the local language (Kannada) to describe convulsions and hypertension, but there were no terms that are specific to pregnancy. Community participants perceived stress, tension and poor diet to be precipitants of hypertension in pregnancy. Seizures in pregnancy were thought to be brought on by anaemia, poor medical adherence, lack of tetanus toxoid immunization, and exposure in pregnancy to fire or water. Sweating, fatigue, dizziness-unsteadiness, swelling, and irritability were perceived to be signs of hypertension, which was recognized to have the potential to lead to eclampsia or death. Home remedies, such as providing the smell of onion, placing an iron object in the hands, or squeezing the fingers and toes, were all used regularly to treat seizures prior to accessing facility-based care although transport is not delayed. Conclusions It is evident that 'pre-eclampsia' and 'eclampsia' are not well-known; instead hypertension and seizures are perceived as conditions that may occur during or outside pregnancy. Improving community knowledge about, and modifying attitudes towards, hypertension in pregnancy and its complications (including eclampsia) has the potential to address community-based delays in disease recognition and delays in treatment that contribute to maternal and perinatal morbidity and mortality. Advocacy and educational initiatives should be designed to target knowledge gaps and potentially harmful practices, and respond to cultural understandings of disease. Trial registration NCT01911494